Merdeka Belajar Di Bali Utara - I Nengah Kresna Dana; Regan Otto Citra; I Made Agus Brastama Andhiriksa; I Nyoman Gede Maha Putra; Nyoman Nuri Arthana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
The independent learning program created by the Ministry of Education and Culture carried out by the Warmadewa University Architecture Study Program is located in the North Bali area. The Merdeka Learning Program in North Bali is the Merdeka Campus program which was first implemented by the Warmadewa University Architecture Study Program with the theme of learning outside the classroom or outside the campus. There are two independent learning programs implemented in the North Bali area, including WAVI-PD, namely research/research on villages in northern Bali and WAVI-PK. WAVI-PK aims to help rural communities who have physical disabilities in the North Bali area.